Bioethanol production from water hyacinth with isolated thermophilic microbial consortium from Kenya - Deffar, Selamawit Shiferaw; Kumar, Anil; Muliwa, Anthony; Pili, Njira Njira; Omara, Timothy (Comptes Rendus. Chimie)
Bioethanol production from water hyacinth pretreated thermochemically through boiling in water with or without sodium chlorite, followed by fermentation with a locally isolated thermophilic bacteria consortium in a partially consolidated bioprocessing was investigated. The time yielding the maximum total reducing sugars was 2 h using 155 mg/g and 113 mg/g of pretreated and untreated water hyacinth samples, respectively. The optimized factors were inoculum dose (8.1%, v/v), temperature (48.8 °C) and time (52.3 h) which resulted into 7.2 g/L of predicted bioethanol concentration. In the experimental run, 7.7 g/L of ethanol was produced, which is close to the predicted value.